Vozes indígenas na educação ambiental: formação de alianças no combate às mudanças climáticas - Diniz, Janelene Freire [UNESP]; Barba, Clarides Henrich de; Oliveira, Keila Ferreira de (Revista Ibero-Americana de Estudos em Educacao, 2024)
This is a fragment of a master's research, with a qualitative approach. This article aims to analyze an intervention action in which it was sought to join forces with indigenous peoples and their powerful voices to collectively reflect on climate change and its triggers, together with eight students from the Degrees in Biology and Chemistry and seven employees of the Federal Institute of Education, Science and Technology of Rondônia. As a theoretical reference, there were used indigenous authors and environmental education authors. Conversation circles were used as a methodology for constructing dialogical spaces during the research. The results showed that providing experiences of different world representations through dialogues with native peoples and forming alliances in confronting the climate threat can contribute to the development of integrated socio-environmental thinking among subjects. It is understood the urgency of including other perspectives in education to face climate change and contemporary crises.